Study Of Starbucks Corporations: Restructuring Challenges And Strategies - Beng, Ching Keng (2009)
Starbucks was chosen as the case study because of its unique and effective business modal and marketing tactics. The case will comprise 2 sections, case writing and case analysis. Starbucks will be described in details in Case Writing section, reviewing their company background, vision, mission statement and its value chain. Case analysis will provide diagnosis on the organization and its related external environment and discussing the possilble reasons for the significant drop in traffic and profits of Starbucks, while suggesting initiatives, actions and strategies to overcome the weakness and threats, and improve the strengths and capture the new opportunities.